ASIAN CATFISH GENUS Pangasius: DIAGNOSIS AND DISTRIBUTION - Rudhy Gustiano; Vitas Atmadi Prakoso; Muhamad Hunaina Fariduddin Ath-thar (Indonesian Fisheries Research Journal, 2018)
Pangasiidae are economically important riverine catfishes that generally exist in freshwater from the Indian subcontinent to the Indonesian Archipelago. Among genera in Pangasiidae, genus Pangasius has numerous species. The objective of the present study is to describe all species of genus Pangasius with their diagnosis and natural distribution. Nine hundred and ninety nine specimens formed the core of the material examined in this study. All examined species were collected from Bangladesh, Vietnam, Cambodia, Thailand, Malaysia, and Indonesia. Additional samples including specimens of 49 previously described species housed in various museums were also examined. On each specimen, 35 point to point measurements covering the possible variation of the body conformation were taken using dial calipers. Measurements were log-transformed before the PCA was run on the covariance matrix. The first factor, considered as the size-factor was not taken into account to minimize the effects of size differences among samples. Allometry is indicated by unequal loading of variables on the first component and by biological interpretation of allometric data proceed using coefficients of the first components against the second components that was linear. An independent PCA was run on the correlation matrix from the untransformed count data. Finally, data analysis consisted in characterizing groups from scatter plots between pairs of structuring characters for subsequent use in generic identification keys. The results show Asian catfish genus Pangasius consist of 21 valid species. This paper describes the diagnosis and distribution of all valid species.